2015
DOI: 10.1056/nejmoa1405760
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI Antisense Oligonucleotide for Prevention of Venous Thrombosis

Abstract: BACKGROUND Experimental data indicate that reducing factor XI levels attenuates thrombosis without causing bleeding, but the role of factor XI in the prevention of postoperative venous thrombosis in humans is unknown. FXI-ASO (ISIS 416858) is a second-generation antisense oligonucleotide that specifically reduces factor XI levels. We compared the efficacy and safety of FXI-ASO with those of enoxaparin in patients undergoing total knee arthroplasty. METHODS In this open-label, parallel-group study, we randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
397
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 541 publications
(413 citation statements)
references
References 18 publications
13
397
0
3
Order By: Relevance
“…However, in patients at or above the 80th percentile, corresponding to ‫ف‬ 50 mg/dl plasma Lp(a) concentrations, much greater reduction than is currently achieved with these indirect therapeutic agents would be required to signifi cantly reduce CVD risk, which is thought to occur at levels which exceed [25][26][27][28][29][30] or OxPL-apoB concentrations, consistent with the independence of lowering of Lp(a) and OxPL-apoB on isoform size ( Fig. 8 ).…”
Section: Alternative Therapies To Lower Lp(a)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in patients at or above the 80th percentile, corresponding to ‫ف‬ 50 mg/dl plasma Lp(a) concentrations, much greater reduction than is currently achieved with these indirect therapeutic agents would be required to signifi cantly reduce CVD risk, which is thought to occur at levels which exceed [25][26][27][28][29][30] or OxPL-apoB concentrations, consistent with the independence of lowering of Lp(a) and OxPL-apoB on isoform size ( Fig. 8 ).…”
Section: Alternative Therapies To Lower Lp(a)mentioning
confidence: 99%
“…1 ). These drugs also have an improved therapeutic index due to reduced pro-infl ammatory properties (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…[24][25][26] Recently, a phase 2 trial demonstrated that FXI-antisense oligonucleotide (FXI-ASO) reduced FXI levels and decreased the incidence of deep vein thrombosis (DVT) after knee arthroplasty without increasing bleeding, thus providing evidence that FXIa can contribute to thrombosis in humans. 27 However, postoperative bleeding in knee arthroplasty is relatively uncommon, and the rate of bleeding with FXI-ASO was not significantly lower than that seen with enoxaparin. 28,29 The FXI-ASO trial demonstrated a role for FXIa in DVT but did not resolve the role of either platelet polyP or FXIIa in postarthroplasty DVT because FXIa can inactivate tissue factor pathway inhibitor, 30 and FXI can be feedback-activated by thrombin.…”
Section: Introductionmentioning
confidence: 94%
“…RNase Hactive ASOs targeting the disease-associated proteins ApoB100, APOCIII, and FXI have produced dosedependent pharmacology in humans, and, in several cases, near complete depletion of these liverderived proteins from plasma has been achieved. [66][67][68][69] Importantly, Kynamro TM , the generation-2 ASO targeting ApoB100, was recently approved for the treatment of homozygous familial hypercholesterolemia, making it the first FDA-approved systemically delivered antisense drug. 67 Moreover, robust clinical efficacy of additional generation-2 ASOs including those targeting APOCIII in the triglyceride pathway and FXI, a regulator of thrombosis, has recently been reported in 2 separate seminal articles in The New England Journal of Medicine.…”
Section: Rna Therapeutics Based On Antisense Principlesmentioning
confidence: 99%
“…67 Moreover, robust clinical efficacy of additional generation-2 ASOs including those targeting APOCIII in the triglyceride pathway and FXI, a regulator of thrombosis, has recently been reported in 2 separate seminal articles in The New England Journal of Medicine. 68,69 As mentioned above, recent advances continue to further the pharmacologic properties, potency, and selectivity of ASO technology and have led to the discovery and clinical evaluation of next-generation cEt ASOs and GalNAc-conjugated ASOs that hold tremendous potential to modulate difficult-to-drug targets in many disease indications including cancer.…”
Section: Rna Therapeutics Based On Antisense Principlesmentioning
confidence: 99%